Belite clinkers with increasing aluminium content: Effect of calcium aluminates on calcium silicate hydration. (December 2022) - Redondo-Soto, Cinthya; Gastaldi, Daniela; Irico, Sara; Canonico, Fulvio; Aranda, Miguel A.G.
Abstract: Belite cements (BCs) could have advantages over Portland cements concerning durability, low heat development and the use of less demanding raw materials. The activation of BCs by sulfur addition at the clinkering stage and by fast cooling is well established. However, the reaction rates of the calcium silicate phases, mainly belite, are still not fully understood. This is partly due to the interplay between factors including: i) belite activation during clinkering; ii) role of the calcium aluminates at early hydration ages; and iii) role of the sulfates. In the research reported here, three belite clinkers were prepared with constant values of lime saturation factor, and SO3, Fe2 O3 and CaF2 contents. The varied parameter was the amount of Al2 O3 . The resulting clinkers have overall crystalline reactive calcium aluminate contents of 0.4, 7.9 and 16.7 wt%, respectively. Cements were prepared with similar particle sizes and constant anhydrite content. Here, it is shown that calcium silicate reactivities, both alite and belite, strongly depend upon the calcium aluminate contents. As these amounts increase, the degree of hydration of alite at 1 day decreases: 85, 65 and 50 %. Furthermore, the degree of hydration of belite at 7 days was 50, 35 and 0 %. Thus, there is a strong influence of aluminates in calcium silicate rates of hydration. Moreover, comparing the mechanical properties of the cements with 0.6 and 8.2 wt% amounts of calcium aluminates, the improvements due to the higher reactivity of calcium aluminates at very early ages, seem to be counterbalanced by the lower reactivity of the silicate phases. The reported findings may allow further optimization of early age reactivity of active BCs.